Caulerpa lentillifera seaweed extract as natural sensitizer for dye-sensitized solar cell - Zakaria, Puteri Najihah Megat; Noor, Ikhwan Syafiq Mohd; Winie, Tan (Wiley-VCH Verlag, 2023)
Chlorophyll natural dye is deemed as an attractive alternative to the expensive and toxic nature Ruthenium-based dyes, due to its abundance in nature. In this work, the chlorophyll is extracted from the Caulerpa lentillifera seaweed. The absorption spectrum of C. lentillifera shows absorbance in 400–450 and 650–700 nm. The acetone produces the highest yield for the C. lentillifera seaweed, followed by ethanol and methanol. The adherence of chlorophyll pigment to the surface of TiO2 is supported by the FTIR, FESEM, and EDX analyses. Dye-sensitized solar cells (DSSCs) are fabricated with poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) based gel-like electrolyte and chlorophyll from C. lentillifera seaweed. The effect of the thickness of the TiO2 mesoporous layer on the light harvesting ability of DSSCs is monitored. The highest efficiency of 0.20% is achieved with a short-circuit current density (Jsc) of 0.52 mA cm−2, the open circuit voltage (Voc) of 0.58 V and the fill factor (ff) of 0.65. The stability of C. lentillifera seaweed extract in DSSCs is reported.